ANALISIS PERILAKU PEMILIH DALAM PEMILIHAN KEPALA DAERAH KABUPATEN KUTAI KARTANEGARA TAHUN 2015 - Efri - novianto (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2017)
AbstractThis research is aimed to analyze the behavior of voters in the regional head election of Kutai Kartanegara of 2015 by discussing the results of the survey and the results of the regional head election of Kutai Kartanegara Regency on December 9, 2015. Based on the research result, the high number of abstain (41.28%) in the election the regional head of Kutai Kartanegara Regency is caused party because of apathy and pragmatic attitude of the voters. While the victory of the candidate Hj. Rita Widyasari, Ph.D - Edi Damansyah is caused by the level of popularity, control of the bureaucratic network, and supported by the political parties the owner of the seat of DPRD Kutai Kartanegara Regency.Keywords: voter behavior, apathy, pragmatic